The impact of branding on corporate identity: a case study of Midlands State University - Mutamiri, Progress (Midlands State University, 2018)
The study focused on the impact of branding on corporate identity on a public university. It sought to establish how the public universities can embrace branding as a way to establish a strong corporate identity and the perceived institutional benefits, differentiation, enhance corporate image, improve corporate reputation as well fight competition in the wake of globalisation, marketization of higher education and existing economic challenges. The study was conducted at Midlands State University’s newly established Zvishavane Campus.The study draws a comparative analysis of branding from established public Universities in Kenya and South Africa.The methodology used in this research was qualitative with data collection from primary sources through the use of interviews, documentary reviews and questionnaire administration as well as from secondary sources through library research and internet. The results revealed that the newly established public universities has resorted to branding not only to enhance a strong corporate identity as branding is alsopart of strategic intangible assets for growth and survival in a competitive environment. The issues of reputation, image and personality has thus brought in a new dimension in the Higher Education sector primarily based on attaining a competitive edge, differentiation and enhance perceived identity of the institution which wholly emanate from the brand. The study concluded that the concept of branding and corporate identity in relation to public universities, is somehow a new phenomenon which is different from branding in the commercial sector.The studyalso revealed dynamics in branding as public universities cannot solely rely on symbols, colours and visual artefacts alone as branding depends on the event, purpose and the message to be communicated.The researcher identified patenting as the major challenge to University branding and recommended that due to the nature of Higher Education Sector branding should be more concerned about creating a who we are for the University which can be equated to the institution's academic reputation as public universities tend to look alike over time and compete less on quality or the price and seek to enhance corporate reputation, strong institutional governance, stakeholder engagement as well as image and personality.